PRODUKSI BIODIESEL DARI LEMAK SAPI DENGAN PROSES TRANSESTERIFIKASI DENGAN KATALIS BASA NaOH - Ranggita Dwi Nindya Affandi; Toni Rizki Aruan; Taslim; Iriany (Talenta Publisher (Universitas Sumatera Utara), 2013)
Biodiesel is an alternative fuel commonly produced from vegetable oil or animal fat with methanol through transesterification. Beef tallow was used as a raw material of transesterification to make biodiesel, because the price of beef tallow was driven down by the market and to reduce the pollution to the surrounding. In this research variable observed were reaction temperature, reaction time and amount of catalyst. Transesterification was carried out in a three necked spherical Pyrex vessel equipped with reflux condenser, stirrer and thermometer. In the present investigation an attempt has been made to use beef tallow as low cost sustainable potential feedstock for biodiesel production by single step transesterification process. Under optimal condition, the maximum yield of 95,67 % beef tallow methyl ester was obtained by using 6 : 1 molar ratio of beef tallow to methanol at 50 oC for a reaction time 30 minutes in the presence of 0,8 wt% of NaOH catalyst. The biodiesel properties were comparable to Indonesian National Standard (SNI). The results of this work showed that the use of beef tallow is suitable for feedstock of biodiesel production with low cost.